Hard places : reading the landscape of America's historic mining districts - Francaviglia, Richard V. (American land and life series., 1997)
Working with the premise that there are much meaning and value in the "repelling beauty" of mining landscapes, Richard Francaviglia identifies the visual clues that indicate an area has been mined and tells us how to read them, showing the interconnections among all of America's major mining districts. With a style as bold as the landscape he reads and with photographs to match, he interprets the major forces that have shaped the architecture, design, and topography of mining areas. Covering many different types of mining and mining locations, he concludes that mining landsca.